New records of Pagurixus Melin, 1939 (Crustacea: Decapoda: Paguridae) from the Ryukyu Islands, southwestern Japan, with description of a new species - Osawa, Masayuki; Kawai, Takashi; Sakamaki, Takashi (Zootaxa, 2013)
Seven hermit crab species of the pagurid genus Pagurixus Melin, 1939 are reported on the basis of material recently col-lected from the northern and central islands of the Ryukyu Islands, southwestern Japan. Four species are new to the hermit crab fauna of the Ryukyu Islands: P. acanthocarpus Komai & Okuno, 2009; P. fasciatus Komai & Myorin, 2005; P. for-mosus Komai, 2010; and P. tweediei (Forest, 1956). One species is described as new to science: P. vicinus sp. nov. is close-ly similar to P. fasciatus in both morphology and coloration, but distinguished by the armature on the left cheliped and right second pereopod. Paguruxus carinimanus Komai & Osawa, 2006 and P. pseliophorus Komai & Osawa, 2006, both previously known from the Ryukyu Islands, are here reported from new localities.